Bromoenol Lactone, an Inhibitor of Calcium-Independent Phospholipase A2, Suppresses Carrageenan-Induced Prostaglandin Production and Hyperalgesia in Rat Hind Paw. (30th April 2015) - Tsuchida, Keiichiro; Ibuki, Takae; Matsumura, Kiyoshi
Abstract : Prostaglandin (PG) E2 and PGI2 are essential to hyperalgesia in inflammatory tissues. These prostaglandins are produced from arachidonic acid, which is cleaved from membrane phospholipids by the action of phospholipase A2 (PLA2 ). Which isozyme of PLA2 is responsible for the cleavage of arachidonic acid and the production of prostaglandins essential to inflammation-induced hyperalgesia is not clear. In this study, we examined the effects of two PLA2 isozyme-specific inhibitors on carrageenan-induced production of PGE2 and PGI2 in rat hind paw and behavioral nociceptive response to radiant heat. Local administration of bromoenol lactone (BEL), an inhibitor of calcium-independent PLA2 (iPLA2 ), significantly reduced carrageenan-induced elevation of prostaglandins in the inflamed foot pad 3 h after injection. It also ameliorated the hyperalgesic response between 1 h and 3 h after carrageenan injection. On the other hand, AACOCF3, an inhibitor of cytosolic PLA2, suppressed neither prostaglandin production nor the hyperalgesic response. BEL did not suppress the mRNA levels of iPLA2 β, iPLA2 γ, cyclooxygenase-2, microsomal prostaglandin E synthase, prostaglandin I synthase, or proinflammatory cytokines in the inflamed foot pad, indicating that BEL did not suppress inflammation itself. These results suggest that iPLA2 is involved in the production of prostaglandins and hyperalgesia at the inflammatory loci.